Effect of Temperature, Media and Light on Germination of Neem (Azadirachta indica A. Juss.) Seeds - Kumar, Devendra; Mishra, Dhruv Kumar; Singh, Balbir (Indian Forester, 2007)
Effect of temperature and media was studied on seed germination of Azadirachta indica (Neem). Germination tests were conducted at four different temperatures viz. 25±1°C, 30±1°C, 35±1°C and 40±1°C with three germination media viz., top of paper (TP), between of paper (BP), and fine sterilized sand. Media and temperature significantly affected seed traits. Seeds germinated well over a wide range of temperature from 25-40±1°C however, significantly higher germination percentage, germination value (GV) and minimum mean germination time (MGT) were obtained at 30±1°C. Lower (25±1°C) and higher (40±1°C) temperatures had adverse effect on germination of Neem seeds. Among media, between paper (BP) was found the best in which maximum germination percentage, minimum MGT and maximum GV was recorded. Sand media was found inferior as compared to top of paper. Seed germination was unaffected with light.